2019
DOI: 10.1177/0895904819843590
|View full text |Cite
|
Sign up to set email alerts
|

Contexts of Belonging: Toward a Multilevel Understanding of Caring and Engagement in Schools

Abstract: Policy makers are increasingly attentive to the importance of supportive school climates, even as many students report that schools seem to be uncaring places. Using recent scholarship that foregrounds the organizational and contextual dimensions of educational caring and student engagement, we use qualitative case study interview data to examine these concepts in two schools. We find that organizational and contextual factors such as students' sense of continuity and the manner and degree of staff collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…As noted above, the data for this study come from case studies of two schools that emphasized caring in their programming and are academically successful, but are otherwise quite different (Stake, 2006). The original purpose of these case studies was to understand how leaders work to create a caring school culture (Ryu et al, 2020), how leaders, teachers and students think about various aspects of belonging (Walls et al, 2021), and how educational professionals productively navigate the micropolitics of caring practice (Walls, 2020). However, the importance of school context/place as it related to organizational learning was an emergent theme in our original coding and did not fit into our initial frameworks.…”
Section: Methods and Research Designmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, the data for this study come from case studies of two schools that emphasized caring in their programming and are academically successful, but are otherwise quite different (Stake, 2006). The original purpose of these case studies was to understand how leaders work to create a caring school culture (Ryu et al, 2020), how leaders, teachers and students think about various aspects of belonging (Walls et al, 2021), and how educational professionals productively navigate the micropolitics of caring practice (Walls, 2020). However, the importance of school context/place as it related to organizational learning was an emergent theme in our original coding and did not fit into our initial frameworks.…”
Section: Methods and Research Designmentioning
confidence: 99%
“…The original purpose of these case studies was to understand how leaders work to create a caring school culture (Ryu et al. , 2020), how leaders, teachers and students think about various aspects of belonging (Walls et al. , 2021), and how educational professionals productively navigate the micropolitics of caring practice (Walls, 2020).…”
Section: Methods and Research Designmentioning
confidence: 99%
“…Finally, to understand students' sense of belonging, we might need to know more about the relationships students have with one another outside science class. This is so, as past research has indicated that students have told investigators that to understand how their peers felt about one another, one needed to understand interactions outside the classroom (Walls et al, 2019). In addition, as we noted at the outset, there may be benefits to silence.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…While this research is insufficiently attentive to the politics of care, there has been even less attention to organizational processes and the particulars of how leaders change minds and change practices (Kurland, 2018; Louis et al, 2016; van der Vyver et al, 2014). Recently, several studies have pointed out this misalignment (Walls et al, 2021) and sought to integrate organizational conceptions of caring school leadership with notions of leadership for social justice (Forde et al, 2021) or social-emotional learning (Kennedy, 2019). However, neither of these studies have directly taken up the work of integrating politically activist caring leadership with organizational conceptions of caring leadership.…”
Section: Caring School Leadership and Critical Carementioning
confidence: 99%
“…Systemically, exclusionary practices hinder the democratic growth of our society in which the perspectives and influence of culturally and linguistically diverse (CLD) communities might be generative of social progress (Riley, 2013). In too many schools, such practices continue to stifle diverse voices by erecting parameters for acceptable behavior and valuable learning based on white, 1 eurocentric norms, thereby positioning Students of Color outside of these norms as unworthy of care ( DeMatthews et al, 2017;Lee, 2017;Rolón-Dow, 2005;Tienken, 2013;Walls et al, 2021;Watkins & Aber, 2009). School leaders may play a role in perpetuating or disrupting such exclusionary practices-including being pushed-out of schools, placed in lower academic tracks, subjected to corporal punishment, underrepresented in curriculum, or stereotyped by teachers-which have disproportionately impacted Black and Brown students 2 (Horning et al, 2015;Morris, 2016;Skiba et al, 2011;Whitaker & Losen, 2019).…”
Section: Introductionmentioning
confidence: 99%